POTENSI DAYA TARIK WISATA DESA WISATA SUNGAI PETAI KABUPATEN KAMPAR - Agustian, Wahyu; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to identify and describe the potential tourist attractions in Sungai Petai Tourism Village, Kampar Regency. The research employs a descriptive qualitative method, using data collection techniques such as observation, interviews, and documentation. The findings indicate that Sungai Petai Village possesses three categories of tourist attraction potential: natural, cultural, and man-made tourism. The most prominent natural attractions are found in dusun Kayu Jangkar, particularly the Petai and Mayor Rivers, which offer clear water, calm flows, and a pristine environment ideal for family recreation and ecotourism. Cultural potential is reflected in the community's social activities, traditional customs, and preserved local values. Meanwhile, man-made attractions are still in the early stages of development. These findings suggest that Sungai Petai Village holds significant opportunities to be developed into a community-based sustainable tourism destination, provided that improvements in infrastructure, promotion, and collaboration between the government and local community are implemented. Keywords: Tourism Potential, Tourist Attraction, Tourism Village, Sungai Petai.